Analysis of Oral Language Variety of Islamic Boarding School Students Darul Muqomqh - Muhammad Wakhidin; Intan Sari Ramdhani (CV. Rayyan Dwi Bharata, 2023)
This study aims to examine the variety of spoken language of students at the Darul Muqomqah Islamic boarding school. In this research, researchers used a qualitative approach and used a descriptive method. The research subject is the variety of spoken language, meanwhile, the object of this research is the variety of spoken language among students. Data collection techniques in this study used recording techniques. Data collected using descriptive qualitative. Data analysis in this study used qualitative data analysis procedures, namely (1) data reduction, (2) data presentation, (3) drawing conclusions. The results of this study found a variety of spoken language among students at the Darul Muqomah Islamic Boarding School. The principles or forms of language found in the Santri language are the variety of standard language, the variety of official language, and the variety of relaxed language.